2010
DOI: 10.1007/s10569-010-9283-5
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid close encounters characterization using differential algebra: the case of Apophis

Abstract: A method for the nonlinear propagation of uncertainties in Celestial Mechanics based on differential algebra is presented. The arbitrary order Taylor expansion of the flow of ordinary differential equations with respect to the initial condition delivered by differential algebra is exploited to implement an accurate and computationally efficient Monte Carlo algorithm, in which thousands of pointwise integrations are substituted by polynomial evaluations. The algorithm is applied to study the close encounter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…One of the key points is that, evaluating a polynomial, the image under the flow of points inside U can be computed very fast. This technique, introduced by M. Berz and K. Makino to study particle accelerators, has been used in several fields, for instance: to study the close approaches of Near Earth Asteroids [3,2] or to compute a Gaussian particle filter for spacecraft navigation [21].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key points is that, evaluating a polynomial, the image under the flow of points inside U can be computed very fast. This technique, introduced by M. Berz and K. Makino to study particle accelerators, has been used in several fields, for instance: to study the close approaches of Near Earth Asteroids [3,2] or to compute a Gaussian particle filter for spacecraft navigation [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that, in the DA-based approach, the Taylor expansion T f shall be computed only once, since the same polynomial can be used in case new statistics need to be mapped. This is an additional advantage with respect to classical MC, as already pointed out in [42].…”
Section: Da-based Monte Carlomentioning
confidence: 80%
“…The differential algebra used for the computations in this work was implemented in the software COSY INFINITY (Berz and Makino 2006). An important application of DA is the automatic high order expansion of the solution of an ODE in terms of the initial conditions (Berz 1999a;Armellin et al 2010). This can be achieved by replacing the operations in a classical numerical integration scheme, including evaluation of the right hand side, by the corresponding DA operations.…”
Section: Differential Algebra and High Order Flow Expansionmentioning
confidence: 99%
“…It was shown that a good agreement with Monte Carlo simulations can be achieved, however the derivation of the dynamics of the high order tensor can be complex from the computational standpoint, especially for high fidelity dynamics. These difficulties were addressed by the authors in past works, in which a technique called differential algebra (DA) was used to automatically expand the flow of the dynamics up to an arbitrary order (Di Lizia et al 2008;Armellin et al 2010). Nonlinear uncertainty propagation can take advantage of the high order expansions of the flow.…”
Section: Introductionmentioning
confidence: 99%